2010
DOI: 10.1111/j.1752-0606.2010.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Parents of Adolescents in Family Therapy: A Qualitative Investigation

Abstract: While understanding clients' experiences in family therapy is becoming increasingly important, we know very little about how the parents of adolescents in family therapy perceive and experience this process. The current study uses a multicase qualitative design and constructivist theoretical framework to describe the experiences of 15 parents of adolescents attending family therapy in private practices. Constant comparative analysis revealed four core categories that described parents' therapeutic experiences:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
2
23
0
1
Order By: Relevance
“…The narrative themes from the earlier study (Lever & Gmeiner, ) indicated that clients who had dropped out reported feeling disconnected, distant, unsafe, unsupported, and disempowered. These results are consistent with those of a more recent investigation (Sheridan, Peterson, & Rosen, ), which identified factors that influenced clients to attend the full course of therapy. Parent participants reported that at the outset of therapy, family members tended to disagree about the nature of the problem, yet they kept coming to sessions because the therapist was “caring, patient, and sincere” and provided direction while validating each individual's knowledge and perceptions.…”
supporting
confidence: 91%
“…The narrative themes from the earlier study (Lever & Gmeiner, ) indicated that clients who had dropped out reported feeling disconnected, distant, unsafe, unsupported, and disempowered. These results are consistent with those of a more recent investigation (Sheridan, Peterson, & Rosen, ), which identified factors that influenced clients to attend the full course of therapy. Parent participants reported that at the outset of therapy, family members tended to disagree about the nature of the problem, yet they kept coming to sessions because the therapist was “caring, patient, and sincere” and provided direction while validating each individual's knowledge and perceptions.…”
supporting
confidence: 91%
“…In comparison to individual therapy, this may be even more important in family therapy, as the alliance in family therapy is typically complex (e.g., Friedlander, Escudero, Heatherington, & Diamond, ; Sexton & Datachi, ). Studies of client experiences in family therapy highlight the importance of personal characteristics of the therapist like humanness, sensitivity, being nonjudgmental, and so on for the therapeutic alliance (e.g., Lever & Gmeiner, ; Sheridan, Peterson, & Rosen, ). It seems that it is of central importance that the family therapist is involved : This means that the therapist is supportive while he/she is also present as a person to confront family members when situations warranted (Sheridan et al., ).…”
mentioning
confidence: 99%
“…Parents' perceptions of blame by providers has also been associated with disruption/termination of treatment episodes (Wolpert 2000;Kuehl et al 1990, Mason et al 1995. Finally, research by Sheridan et al (2010) into parental perceptions of treatment identified that therapist who exhibit non-judgmental, nonblaming qualities improve the comfort that parents experience with the therapeutic process. Feinstein et al (2009) identify a paucity of professional literature providing guidance to clinicians on how best to develop and sustain effective parent-clinician alliances.…”
Section: Guilt and Blamementioning
confidence: 98%